Characterization of radiochromic poly(vinyl-alcohol)–glutaraldehyde Fricke gels for dosimetry in external x-ray radiation therapy. (22nd March 2019) - Gallo, Salvatore; Artuso, Emanuele; Brambilla, Maria Grazia; Gambarini, Grazia; Lenardi, Cristina; Monti, Angelo Filippo; Torresin, Alberto; Pignoli, Emanuele; Veronese, Ivan
Abstract: Quality assurance procedures required in modern radiotherapy would greatly benefit from the development of tissue equivalent dosimeters able to render three-dimensional dose profiles with a high spatial resolution. In this scenario, Fricke gel (FG) dosimeters could be good candidates, but some limitations have restricted their use in clinical practice. Recently, formulations based on gel matrices of poly(vinyl-alcohol) (PVA) chemically cross-linked with glutaraldehyde (GTA) have shown improvements compared to FGs with natural matrices. The purpose of this study is the characterization of the dosimetric properties of radiochromic PVA–GTA FG dosimeters by means of absorption spectroscopy measurements. Xylenol orange (XO) FG dosimeters, prepared in spectrophotometry cuvettes using 9.1 w/w of Mowiol ® -PVA and 26.5 mM of GTA, were uniformly irradiated with a 137 Cs source and with 6 and 15 MV x-rays generated by a medical linear accelerator. Ultraviolet–visible absorbance spectra collected at consecutive times post-irradiation showed that a time of approximately 15 min is sufficient to reach a stable absorbance value, indicating the achievement of a chemical equilibrium in the complexation processes between Fe 3+ and XO. The analysis of the change of the absorbance spectra shape with the cumulated dose demonstrated that a linear dose–response curve of PVA–GTA FG dosimeters is obtained in the entire investigated dose interval of 0.5–15 Gy by properly choosing the wavelength used for the absorbance measurements. Furthermore, PVA–GTA FG dosimeters proved to be nearly water- and tissue-equivalent and characterized by a response independent of the energies and dose rates in the investigated intervals. These findings suggested that PVA–GTA FGs are promising tools for dosimetry applications in external x-ray radiation therapy.